Educational and Social Innovation in Family Promotion of Personal Autonomy in Older Adults: the PCF-U-Auto - Nevot-Caldentey, Lluc; Orte, Carmen; Ballester, Lluís; Amer, Joan (Revista Complutense de Educación, 2021)
The goal of this study was to design and evaluate the 1st pilot of the Universal Family Competence Program Auto (PCF-U-Auto), aimed at promoting the personal autonomy of older adults without or with incipient symptoms of dependence in different locations in Mallorca. The study had a quasi-experimental design and focused on three aspects: a) process measures; fidelity, adherence and involvement records per session and participant, b) measures of change on the variables that measure family dynamics and skills related to the promotion of autonomy; pre-test / post-test evaluation on the Social Resources Scale, Family Function Questionnaire, Quality of Life Questionnaire and Depression Scale evaluated on older adults; and (c) outcome measures; satisfaction levels of the participants. The results confirm the validity of the Universal Auto Family Competence Program as a tool for family prevention of dependency situations in adulthood.